Information quantifiers for trapped ion in a carrier excitation laser field - Raffah, Bahaaudin M.; Khalil, E. M.; Abdel-Khalek, S.; Berrada, K.; Al-Hadeethi, Yas; Ali, Ahmad T.; Mohamed Ridza Wahiddin (World Scientific Publ Co Pte Ltd, 2024)
Indexed by WOS